An apprenticeship in arms the origins of the British Army 1585-1702 - Manning, Roger B. (Roger Burrow); Oxford eBooks (Oxford : Oxford University Press, 2006)
This text is a scholarly study of the military experiences of peers and gentlemen from the British Isles who volunteered to fight in the religious and dynastic wars of mainland Europe, as well as the ordinary men who served from the time of the English intervention in the Dutch war of independence to the death of William III.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Great Britain. -- Army -- History -- 17th century; Great Britain -- Armed Forces -- History; Great Britain -- History, Military -- 1485-1603.; Great Britain -- History, Military -- 1603-1714.; Electronic books